Managing end of life medications at home—accounts of bereaved family carers: a qualitative interview study. Issue 2 (25th September 2014) - Payne, Sheila; Turner, Mary; Seamark, David; Thomas, Carol; Brearley, Sarah; Wang, Xu; Blake, Susan; Milligan, Christine
Abstract : Objective: To explore how bereaved family members recall managing end of life medications when delivering care to a patient dying at home in England. Design: Qualitative study. Setting: Domestic homes in two contrasting areas in England. Participants: 59 bereaved family carers who have delivered care to a patient who spent a minimum of 2 weeks at home prior to their death from cancer or other non-malignant condition. Cases were excluded if the place of death was: a hospice, nursing home or National Health Service (NHS) hospital. Results: Participants identified a number of important concerns about managing end of life medication for the dying person at home. Although some support with medications is provided by general practitioners and nurses in the community, family carers take primary responsibility for drug administration and storage. They reported anxiety about giving correct and timely dosages, and concerns about keeping the patient comfortable without overdosing them or risking shortening their lives. In particular, they reported that certain analgesic medications, especially opioids, were considered to have a symbolic significance increasing analgesia requirements, and the use of a syringe driver was associated with deterioration and approaching death. Key barriers to managing end of life medications at home included: complex regimes; unwanted responsibility in deciding when to use 'as needed' medication; disagreements with professional staff, and anxiety about medication errors, especially if perceived to have implications for survival. Conclusions: Family carers require more information about end of life drugs and their effects, support and training in managing medication for a dying person.